ANALISIS KESALAHAN SISWA SEKOLAH MENEGAH ATAS DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI PROGRAM LINEAR BERDASARKAN PROSEDUR NEWMAN - Ananda Nadya Widyaloka, - (2022)
In everyday life mathematics has an important role in human life. By studying mathematics, it is expected to form human characters who are thorough, logical, creative, innovative and never give up. This research is related to the analysis of errors and factors that cause students to make errors in solving math problems. This research was conducted in one of the private high schools located in the city of Bandung in class XI students of the 2022/2023 academic year in odd semesters. The subjects of this study were 8 students from 21 students who took the test to solve math problems. The research uses a qualitative approach with a case study method. The data generated is descriptive data with document instruments, tests, and interviews. The results of the study revealed that there were errors made by students in solving contextual math problems. By using the Newman procedure, errors are divided into 5 types, namely: 1) reading error, the percentage of error is 12.70%, 2) comprehension error is 46.03%, 3) transformation error. problem (transformation) with an incorrect percentage of 38.10%, 4) error of procedure/process skills (process skill) with an incorrect percentage of 49.21% and 5) final answer error (enconding) with a percentage of 63.49%. The average percentage of all errors is 41.90%, which means that almost half of the students make mistakes in solving contextual math problems. The factors that cause students to make mistakes are: the questions given by the teacher lack innovation, the internal causes of students are less able to motivate themselves so that they fall asleep in class and are not reprimanded, he finds it difficult to make what is known and asked, the form of story questions that feel long makes the student is less literate, the student forgets the completion steps, the student forgets to write down the final answer and the student is in a hurry to complete the test. Keywords: Student Errors, Solving Problems, Newman Analysis